2016
DOI: 10.1097/icl.0000000000000212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smoking on Central Corneal Thickness and the Corneal Endothelial Cell Layer in Otherwise Healthy Subjects

Abstract: Although cigarette smoking has no effect on cell polymorphism and polymegethism, the results suggest that smoking reduces endothelial cell count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Smoking is prevalent among Egyptian men much more than Egyptian women [36]. This assumption was tested by Sayin et al who revealed a lower percentage of endothelial hexagonal cells observed in smokers than nonsmokers ( P < 0.001) [37] and Ilhan et al who found decreased ED and Hex, with increased CV in smokers versus nonsmokers [38].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is prevalent among Egyptian men much more than Egyptian women [36]. This assumption was tested by Sayin et al who revealed a lower percentage of endothelial hexagonal cells observed in smokers than nonsmokers ( P < 0.001) [37] and Ilhan et al who found decreased ED and Hex, with increased CV in smokers versus nonsmokers [38].…”
Section: Discussionmentioning
confidence: 99%
“…Golabchi et al reported that smoking results in an increased CV and decreased ECD (15). Ilhan et al (16) reported that smoking does not affect the CCT, CV, and percentage of hexagonality values, but there was a significant reduction in ECD in smokers. However, Kara et al (17) did not determine any significant difference between smokers and non-smokers regarding the mean ECD or parameters of endothelial cell morphology.…”
Section: Discussionmentioning
confidence: 98%
“…Aging, intraocular surgery, trauma, glaucoma, smoking and alcohol decrease the number of endothelial cells, and cause morphological changes in the endothelial cell layer (13)(14)(15). Endothelial cell analysis is important to evaluate corneal function and viability.…”
Section: Discussionmentioning
confidence: 99%